Pengaruh Penerapan Metode Writing In Here And Now Terhadap Hasil Belajar Alqur’an Hadits Siswa SMP Swasta Yayasan Perguruan Utama Medan - Laila, Annisa Fitra (Universitas Labuhanbatu, 2024)
Education is a conscious and planned effort to create a learning atmosphere and learning process in such a way that students can actively develop their potential so that they have self-control, intelligence, skills in society, religious spiritual strength, personality and noble morals. Al-Qur'an Hadith is part of the Islamic religious education subject which emphasizes the ability to read and write the Al-Qur'an and Hadith correctly as well as memorizing short letters in the Al-Qur'an, introducing simple meanings or meanings. from letters in the Qur'an and hadiths to be understood and put into practice in everyday life through example and habit. Learning for students is the process of building their own ideas or understanding, so learning activities should provide opportunities for students to carry out teaching and learning activities smoothly and with motivation. The location of this research was at YP Utama Private Middle School located at Jalan Suluh No. 80A, SidorejoHilir, Medan Tembung District, Medan City. The research will be carried out starting in the odd semester of the 2023/2024 academic year. The population in this study was all 24 students in class VII of YP Utama Medan Middle School, academic year 2023/2024. The sample in this study was 24 students taken from the entire population. Based on the results of the T test on the posttest data, it shows that the learning outcomes of class VIII students are significant 001 < 0.05, it can be concluded that Ha is accepted. Thus, it is known that there are research results showing a significant influence between those who received treatment using the writing in here and now method and those who did not use the writing in here and now method. As for student learning outcomes seen from the test questions before getting the method, they could only answer 5-7 questions. With the writing in here and now method, students could answer 10-20 questions.